Listeria monocytogenes-reactive T lymphocyte clones with cytolytic activity against infected target cells (The Rockefeller University Press, 1986)
Lyt-2+ T cell clones were established from Listeria monocytogenes- infected mice. The clones secreted IFN-gamma after stimulation with spleen cells from L. monocytogenes-infected mice plus IL-2. Spleen cells from normal mice were not stimulatory. Furthermore, cloned T cells lysed L. monocytogenes-infected macrophages. Cytolysis was antigen-specific and H-2K-restricted. These findings suggest a role for specific cytotoxic T cells in the immune response to intracellular bacteria.